Modular multilevel converter dc fault protection - Cwikowski, Oliver (2020)
High-voltage direct current (HVDC) grids will require the development of dc protections that provide fast fault isolation and minimize the disturbance caused to the existing ac power networks. This paper investigates how the dc fault recovery performance of a half-bridge modular multilevel converter (HB-MMC) is impacted by different dc protection design choices. An HB-MMC point-to-point HVDC system that is protected with dc circuit breakers (CBs) is simulated on a real-time digital simulator using detailed switch models of the converters and switch gear. A dc CB controller has been developed and implemented in a software-in-the-loop fashion, and has been made available free for download. A novel blocking scheme for the HB-MMC is proposed, which limits the prospective dc-side fault current, benefiting dc switch gear. A comparison of circulating current controllers shows that the standard d - q controller is likely to be unsuitable for fault studies. Finally, benchmarking shows that a 48% reduction in power-flow recovery time and a 90% reduction in the energy dissipated in the circuit breaker can be achieved, along with other benefits, depending on the protection design.